Pain and pleasure in Ibn – Zaidoon poetry (Journal of the College of Languages (JCL), 2008)
Pain and pleasure is when a human being feels pain because one of his sensesُ organs has extremely stressed itself. Where as pleasure is when someone indulges himself as much as he could and get away from anything that causes pain to himself and hurts it. The beauty of the poetic text appears when two contradictions occur together in the same poetic line, just like when two contradictions live together in life; they live and struggle in one poem. Contradictory duet is not something new poetry was based on this duet since it was found until this day. It forms the essential source from which meanings come, and the guide lines that drawn by the personal experience of the poet are formed from it.I preferred to study the duet of Ibn- Zaidoonُ s poetry because he is on of the outstanding poets of the fifth century I found it in his poet texts to discover the hidden sides of the poet and how progressive and classy his mentality has become.